Sociology of Entrepreneurship and Beyond: An Interview with Gyorgy Lengyel - Gyorgy Lengyel (Экономическая социология, 2015)
Prof. Lengyel was interviewed by Maxim Markin, junior research fellow at the National Research University Higher School of Economics in Moscow. Prof. Lengyel was asked about changes in major research streams in Hungarian economic sociology since 2002 when he gave his first interview to the Journal of Economic Sociology. In this interview, Prof. Lengyel notes that the Hungarian tradition of economic sociology tends to remain pragmatic. However, Hungarian sociology obviously has become more internationalized due to scholars’ participation in international research projects, the establishment of peer-reviewed journals, and offering English-based MA and PhD programs. In addition, Prof. Lengyel emphasizes that entrepreneurship — along with employment policy, migration, and unemployment — remains a popular topic for sociological research. He proposes that the decline of entrepreneurship inclination among adults observed in European countries can be explained by a number of reasons, including a low level of general trust and crises. At the same time, European integration contributed to the emergence of new social categories such as supranational elites and globalized classes, which have rarely been in the center of sociological studies. Finally, Prof. Lengyel expects that such topics as economic behavior and its social implications under crises will attract serious attention from economic sociologists in the near future.